Therapeutic effects of olive leaf tea (Olea europaea L.) on gastrointestinal symptoms and body composition in adults with small intestinal bacterial overgrowth - Zafar, Ayesha; Ahmed, Waqas; Tahir, Sajid Khan; Ahmad, Abdul Momin Rizwan; Iqbal, Sanaullah (Frontiers in Nutrition, 2025)
IntroductionOlive leaf has strong antibacterial and anti-inflammatory properties, potentially modulating gut microbiota composition. This may help address small intestinal bacterial overgrowth (SIBO), a gastrointestinal (GI) problem causing malabsorption and potential complications.ObjectiveThis study aimed to observe the effect of olive leaf tea (OLT) on GI symptoms, body composition, and the hydrogen/methane breath test among patients suffering from SIBO.MethodsA total of 49 SIBO individuals, confirmed after a glucose breath test (GBT), were divided randomly into two groups. The treatment group (n = 25) took OLT (1.7 g leaf powder/250 mL water) twice/day for 2 months, and the control group (n = 24) was given no tea. After the intervention, GBT was conducted, and symptoms were assessed through the GI symptom rating scale (GSRS) and symptomatic questionnaire, and body composition parameters were assessed. The area under the curve, chi-square, independent, and paired sample t-tests were performed for data analysis.ResultsIn the intervention group, there was a significant decrease observed in GSRS score (from 19 to 6.8), symptomatic score (4.1 to 1.7), H2/CH4 peak (20.8–5.7 ppm), mean H2 (p = 0.0041) and mean H2 + CH4 production (p = 0.0043), with 88% GBT normalization rate (p = 0.001), as compared to the control group. A significant decrease in weight, TBW, BMR, and muscle mass was also documented (p < 0.05).ConclusionThis study concludes that OLT consumption might have therapeutic benefits against SIBO by alleviating symptoms and normalizing GBT, but does not significantly improve body composition parameters.